Expansion and Divergence of Argonaute Genes in the Oomycete Genus Phytophthora - Bollmann, Stephanie R.; Press, Caroline M.; Tyler, Brett M.; Grünwald, Niklaus J. (Frontiers in Microbiology, 2018)
Modulation of gene expression through RNA interference is well conserved in eukaryotes and is involved in many cellular processes. In the oomycete Phytophthora, research on the small RNA machinery and function has started to reveal potential roles in the pathogen, but much is still unknown. We examined Argonaute (AGO) homologs within oomycete genome sequences, especially among Phytophthora species, to gain a clearer understanding of the evolution of this well-conserved protein family. We identified AGO homologs across many representative oomycete and stramenopile species, and annotated representative homologs in P. sojae. Furthermore, we demonstrate variable transcript levels of all identified AGO homologs in comparison to previously identified Dicer-like (DCL) and RNA-dependent RNA polymerase (RDR) homologs. Our phylogenetic analysis further refines the relationship of the AGO homologs in oomycetes and identifies a conserved tandem duplication of AGO homologs in a subset of Phytophthora species.